Examining The Influence Between Governance Quality and Hunger Levels in African Countries 1998-2022 - Kristiana, Dinda Maria (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2025)
Abstract Hunger is one of the persistent problems in Africa. One of the key factors contributing to the ongoing hunger crisis in Africa is the poor quality of governance in its countries. The better the quality of governance, the better the level of democracy within a country. This study aims to identify the influence of good governance on hunger levels in African countries from 1998–2022. Good governance is assessed using six indicators from the Worldwide Governance Indicators (WGI), which include Voice and Accountability, Political Stability and Absence of Violence/Terrorism, Government Effectiveness, Regulatory Quality, Rule of Law, and Control of Corruption. This study employs a quantitative method with multiple linear regression analysis to explore the relationship between each WGI indicator and hunger levels, measured using the Global Hunger Index (GHI). The research hypothesis suggests that all WGI indicators significantly influence hunger levels in African countries. However, the results reveal that not all WGI indicators have a significant impact on hunger levels in these countries. Keywords: Africa, Good Governance, Hunger Abstrak Kelaparan adalah salah satu masalah berkepanjangan yang terjadi di Afrika. Salah satu hal yang menyebabkan masalah kelaparan bisa terus terjadi di Afrika adalah buruknya kualitas pemerintah di negara-negara Afrika. Semakin baik kualitas suatu pemerintahan, maka semakin baik pula tingkat demokrasi yang ada di negara tersebut. Penelitian ini bertujuan untuk mengidentifikasi pengaruh good governance terhadap tingkat kelaparan di negara-negara Afrika selama periode 1998–2022. Good governance dinilai menggunakan enam indikator dari Worldwide Governance Indicators (WGI) yang mencakup Voice and Accountability, Political Stability and Absence of Violence/Terrorism, Government Effectiveness, Regulatory Quality, Rule of Law, dan Control of Corruption. Penelitian ini menggunakan metode kuantitatif dengan analisis regresi linier berganda untuk mengeksplorasi keterkaitan antara masing-masing indikator WGI dan tingkat kelaparan yang diukur berdasarkan Global Hunger Index (GHI). Hipotesis penelitian mengatakan jika semua indikator dalam WGI berpengaruh signifikan terhadap tingkat kelaparan negara-negara Afrika namun hasil dari penelitian menunjukkan jika tidak semua indikator WGI berpengaruh terhadap tingkat kelaparan negara-negara Afrika. Kata kunci: Afrika, Kelaparan, Kualitas Pemerintah